The formation pathways of aqueous hydrogen peroxide in a plasma-liquid system with liquid as the cathode. (30th August 2018) - He, Xinyi; Lin, Jiao; He, Bangbang; Xu, Le; Li, Junshuai; Chen, Qiang; Yue, Guanghui; Xiong, Qing; Liu, Qing Huo
Abstract: Using an aqueous solution of NaCl as the cathode, we explored the atmospheric pressure Ar discharge plasma generated above the solution surface. The formation pathways of aqueous hydrogen peroxide (H2 O2aq ) in this system were investigated. Dimethyl sulfoxide was used as a scavenger of hydroxyl (OH) radicals to investigate the contribution of dissolved OH radicals to the H2 O2aq . The results indicate that the H2 O2aq is mainly formed by the combination of the dissolved OH radicals at the plasma-affected thin liquid layer, while the H2 O2 formed in the gas phase and the H2 O2aq formation inside water by the plasma-induced ultraviolet radiation have no contribution.